Spatiotemporal evolution of island ecological quality under different urban densities: A comparative analysis of Xiamen and Kinmen Islands, southeast China. (May 2021) - Liu, Chao; Yang, Minghui; Hou, Yuting; Zhao, Yuning; Xue, Xiongzhi
Highlights: Xiamen Island's ecological quality has remained stable and even improved slightly during 1995 to 2016. Xiamen Island's ecological quality is closely correlated with its urban planning policy. Kinmen Island has suffered different levels of reduction of the ecological quality during 1995 to 2016. For Kinmen Island, Xiamen's ecological environment governance experiences are worth learning. RSEI values are positively correlated with greenness and humidity and negatively correlated with heat and dryness. Abstract: Island ecosystems are increasingly threatened by pressures from both climate change and intensifying human activity, especially in developing countries. Evaluation of ecological quality is essential to implementation of interventions for adapting to climate change and alleviating human–nature land-use conflicts in the Anthropocene era. However, the temporal and spatial characteristics of island ecological quality, including variation arising from anthropogenic perturbations, climate change effects, and spatiotemporal heterogeneity, are rarely given serious attention. This study compares Xiamen Island and Kinmen Island, two neighboring islands with pronounced differences in urban density, adopting a Remote Sensing Ecological Index (RSEI) to describe the spatiotemporal differences in island ecological quality. The results show that the RSEI was positively correlated with greenness and humidity and negatively correlated with heat and dryness. Despite the fact that Xiamen Island has experienced extensive urban expansion and rapid population growth, its ecological quality has remained stable and even improved slightly, which mainly due to scientific urban planning. Despite the ecological advantages of its less urban setting, Kinmen Island has suffered reduced ecological quality due to deterioration of natural conditions, climate warming, and increasing human activity. These research findings provide empirical evidence for the need for scientific and systematic urban planning in high-density urban areas and serves as an important reference for planners and decision-makers for effective improvement in the ecological quality of Kinmen Island.